A troubleshooting guide for writers strategies and process - Clouse, Barbara Fine (McGraw-Hill, 2009)
A troubleshooting guide to prewriting; How do I write a thesis? How do I get my ideas to fit together? A troubleshooting guide to drafting... A troubleshooting guide to revising. A troubleshooting guide to editing. A troubleshooting guide to research.